Highly Flexible and Efficient Solar Steam Generation Device. Issue 30 (12th June 2017) - Chen, Chaoji; Li, Yiju; Song, Jianwei; Yang, Zhi; Kuang, Yudi; Hitz, Emily; Jia, Chao; Gong, Amy; Jiang, Feng; Zhu, J. Y.; Yang, Bao; Xie, Jia; et al.
Abstract : Solar steam generation with subsequent steam recondensation has been regarded as one of the most promising techniques to utilize the abundant solar energy and sea water or other unpurified water through water purification, desalination, and distillation. Although tremendous efforts have been dedicated to developing high‐efficiency solar steam generation devices, challenges remain in terms of the relatively low efficiency, complicated fabrications, high cost, and inability to scale up. Here, inspired by the water transpiration behavior of trees, the use of carbon nanotube (CNT)‐modified flexible wood membrane (F‐Wood/CNTs) is demonstrated as a flexible, portable, recyclable, and efficient solar steam generation device for low‐cost and scalable solar steam generation applications. Benefitting from the unique structural merits of the F‐Wood/CNTs membrane—a black CNT‐coated hair‐like surface with excellent light absorbability, wood matrix with low thermal conductivity, hierarchical micro‐ and nanochannels for water pumping and escaping, solar steam generation device based on the F‐Wood/CNTs membrane demonstrates a high efficiency of 81% at 10 kW cm −2, representing one of the highest values ever‐reported. The nature‐inspired design concept in this study is straightforward and easily scalable, representing one of the most promising solutions for renewable and portable solar energy generation and other related phase‐change applications. Abstract : A nature‐inspired steam‐generation material of flexible wood/CNTs composite membrane is developed directly from natural wood. Systematic optimizations of water transportation, thermal management, and light absorption and thus high water evaporating efficiency can be realized by using the nature‐made channels in wood for efficient water transportation, intrinsic thermal‐insolating wood matrix as thermal barrier, and CNT‐coated surface as light absorber.